(untitled) (Revista História & Perspectivas, 2009)
Resenha da obra: MACIEL, Laura, ALMEIDA, Paulo R.; KHOURY, Yara & (Org.). Outras histórias: memórias e linguagens. Säo Paulo: Olho D’Agua, 2006. 298 p.